2015
DOI: 10.1186/s12906-015-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Soshiho-tang water extract inhibits ovalbumin-induced airway inflammation via the regulation of heme oxygenase-1

Abstract: BackgroundSoshiho-tang, known as Xio-hai-Hu-Tang in Chinese and Sho-Saiko-to in Japanese, has been widely used as a therapeutic agent. Its pharmacological effects include anti-inflammatory, antioxidant, antihepatic fibrosis, antitumor and immunomodulating activities. However, little is known regarding its effects on allergic asthma. Therefore, the aim of the present study was to investigate whether the Soshiho-tang water extract (SSTW) has antiasthmatic effects on airway inflammation in an ovalbumin (OVA)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…HO-1 has been shown to attenuate symptoms in AD-like lesions mice model (Kirino et al, 2008). Recent studies have shown that SST highly increases HO-1 protein expression (Jeon et al, 2015). In the present study, we also observed that SST increased HO-1 protein expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 has been shown to attenuate symptoms in AD-like lesions mice model (Kirino et al, 2008). Recent studies have shown that SST highly increases HO-1 protein expression (Jeon et al, 2015). In the present study, we also observed that SST increased HO-1 protein expression.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several pharmacological activities of SST have been reported. According to previous experimental studies, this herbal prescription effects treatment of chronic hepatitis (Kusunose et al, 2002) and liver cirrhosis (Chen et al, 2004; Chen et al, 2005) and exhibits a variety of pharmacological properties including anti-inflammatory (Amagaya et al, 1986; Oh et al, 2013), antioxidant (Sakaguchi et al, 1993), anti-tumor (Zhu et al, 2005), anti-obesity (Yoo et al, 2016), anti-asthmatic (Jeon et al, 2015), and immune-regulative activities (Taira et al, 2004; Kang et al, 2009). In addition, SST showed no significant variation between contents depending on the storage period.…”
Section: Introductionmentioning
confidence: 99%
“…SST was traditionally used to control febrile diseases in several Asian countries. 1 Recent studies support the notion that SST has potential anti-tumor, 2 , 3 , 4 , 5 anti-inflammatory, 6 , 7 , 8 immune regulatory, 9 , 10 and hepatoprotective 5 , 7 activities in preclinical investigations. Most clinical studies using SST have shown its efficacy for liver problems such as hepatic dysfunction, 11 chronic liver diseases, 12 hepatitis B and C, 13 , 14 and liver cancer.…”
Section: Introductionmentioning
confidence: 84%
“…To date, a variety of HO-1 activator can be extracted from Saururus chinensis [ 54 , 55 ], Phytolacca esculenta [ 68 ], Garlic [ 40 ], and soshiho-tang [ 73 ]. Among them, diallyl-disulfide (isolated from Garlic ) [ 40 ] and esculentoside A (isolated from Phytolacca esculenta ) [ 68 ] have been further proved as Nrf-2 activators.…”
Section: Basic Researchesmentioning
confidence: 99%